Architectural designing and planning. (3G E-learning LLC, 2023)
"Architecture involves a lot of strategy and planning. From the beginning, business owners, architects, and construction management must work together to find a cohesive project that fits everyone's standards. While it may seem like a given to put thought behind the planning process, some don't realize how helpful the art of master planning can be to any given project. Architectural master planning is the critical first step in any design process. It is the creation of a framework in which the whole project proceeds. Headed by a lead architect, a project's planning phase considers the entire picture through detailed work. The process involves examining the design and style of the building, surrounding infrastructure, local government requirements, and so on It should also include determining the purpose of the structure, goals of the project, and other essential elements. By creating a master plan, the entire project is likely to go as planned and lead to an exciting development. Now, let's discuss how master planning in architecture benefits everyone involved, including construction workers, future tenants, and beyond. This book deals with the features of designing and improving the spatial and planning structure of the dwelling and residential development in conditions of complex terrain, taking into account orographic features of the structure and climatic conditions."--Back cover